2017
DOI: 10.1371/journal.pone.0174309
|View full text |Cite
|
Sign up to set email alerts
|

Knocking-down of CREPT prohibits the progression of oral squamous cell carcinoma and suppresses cyclin D1 and c-Myc expression

Abstract: BackgroundAs a regulator essential for many cell cycle-related proteins, the robust expression of Cell cycle-Related and Expression-elevated Protein in Tumor (CREPT) implicates a poor diagnosis of endoderm and mesoderm-derived tumors. Whether CREPT plays the same role in the tumorigenesis derived from ectodermal tissues remains elusive.MethodsTo explore the role of CREPT in ectoderm-derived tumors, cells from 7oral squamous cell carcinoma (OSCC) lines and 84clinical OSCC samples were exploited in this study. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Knockdown of CREPT inhibits the proliferation and migration of non-small cell lung cancer cells, whereas overexpression of CREPT demonstrates an oncogenic effect (21,43). Similarly, an oncogenic function of CREPT has been observed in oral squamous cell carcinoma and gastric cancer (22,44). Notably, CREPT has been reported to be highly expressed in HCC tissues and cell lines (16).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Knockdown of CREPT inhibits the proliferation and migration of non-small cell lung cancer cells, whereas overexpression of CREPT demonstrates an oncogenic effect (21,43). Similarly, an oncogenic function of CREPT has been observed in oral squamous cell carcinoma and gastric cancer (22,44). Notably, CREPT has been reported to be highly expressed in HCC tissues and cell lines (16).…”
Section: Discussionmentioning
confidence: 80%
“…A high expression level of CREPT is correlated with tumor stage, metastasis and a poor survival rate (1921). Previous studies have demonstrated that CREPT promotes tumor growth in vivo and in vitro by accelerating cell growth and cell cycle progression (22,23). Therefore, CREPT may serve as a potential and promising target for the development of anticancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The protein expression levels of Wnt target genes including cyclin D1, VEGF, c-myc and survivin were enhanced after CIH treatment in a mouse model of lung cancer [21][22][23][24] . Cyclin D1 regulates the cell cycle by controlling G1/S transition, and the up-regulation of cyclin D1 is related to the development of various cancers 42,43 . C-Myc is an oncogenic transcription factor, recognizing E-box and related sequences in the promoters of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Human oral keratinocyte (HOK) cells (ScienCell Research Laboratories, Carlsbad, CA, USA) were used as a normal control (28). The LSCC cell lines were grown in RPMI-1640 (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA; cat.…”
Section: Methodsmentioning
confidence: 99%